Cold agglutinin disease: current challenges and future prospects - Berentsen, Sigbjørn (J Blood Med, 2019)
Cold agglutinin disease (CAD) is a complement-dependent, classical pathway-mediated immune hemolytic disease, accounting for 15–25% of autoimmune hemolytic anemia, and at the same time, a distinct clonal B-cell lymphoproliferative disorder of the bone marrow. The disease burden is often high, but not all patients require pharmacological treatment. Several therapies directed at the pathogenic B-cells are now available. Rituximab plus bendamustine or rituximab monotherapy should be considered first-line treatment, depending on individual patient characteristics. Novel treatment options that target the classical complement pathway are under development and appear very promising, and the C1s inhibitor sutimlimab is currently being investigated in two clinical Phase II and III trials. These achievements have raised new challenges and further prospects, which are discussed. Patients with CAD requiring therapy should be considered for clinical trials.